Predicting the unpredictable: analysing the entropy and spatial distribution of ball movement patterns in field hockey - Lord, Felicity; Pyne, David; Welvaert, Marijke; Mara, Jocelyn (Biology of Sport, 2023)
Analysing the ball movement patterns of team invasion sports provides practical insight into successful strategies by identifying how and where to move the ball to create goal scoring opportunities. The aim of this study was to analyse the entropy and spatial distribution of ball movement patterns in international field hockey teams. A notational analysis system was developed in SportsCode to analyse 131 matches (n = 57 men, n = 74 women) from the 2019 Pro League tournament. The start and end location of each ball movement and the outcome of each play was recorded. Calculated variables included game possession (%), entropy, possession per zone (%) and progression rates. Decision trees identified that higher circle possession and direct movements to goal from deep attack, and lower build attack and build defence entropy, were the strategies most likely to to goal shots. However, teams should be unpredictable when the opposition are organised to maintain possession and unbalance the defence. Match context only had small effects on ball movement strategies highlighting there is more than one way to be successful. Exeleadcuting strategies that exploit these factors should lead to greater attacking opportunities and success. Analysing the dynamic, complexity of international hockey allows coaches to prepare specific strategies for individual teams.